An In Vivo Study on the Development of Bacterial Microbiome on Clear Orthodontic Retainer - Kabilan Velliyagounder; Anil Ardeshna; Serena Shah (MDPI AG, 2022)
Objectives: The objective of this study was to see how the bacterial composition changes on clear orthodontic retainer over a 14-day period. Methods: Saliva and plaque samples collected from a clear retainer surface were obtained from five healthy volunteers receiving retainer treatment. Prior to clear retainer delivery, patients had not been wearing any other appliances. Patients were instructed to wear their clear retainer for the 14-day period, taking them off to eat and to clean them with a soft-bristle toothbrush. The bacterial composition was determined via Illumina MiSeq sequencing of the bacterial 16S rRNA. After bioinformatics processing using the QIIME pipeline, the intra- and intergroup biodiversity of the sample was analyzed. Results: The bacterial composition changed over a 14-day period in the saliva and on the clear retainer. When comparing the different phylum levels between saliva and clear retainer' microbiota, the Firmicutes were significantly increased 1.26-fold (p = 0.0194) and 1.34-fold (p = 0.0123) after 7 and 14 days of retainer treatment when compared to saliva, respectively. The Campylobacteriota were significantly decreased 1.80-fold (p = 0.05) in the clear retainer when compared to saliva at 7 days. At the genus level, several microbiota were significantly increased in relative abundance in the clear retainer after the 14-day period. Conclusion: These findings reveal that the presence of a clear retainer in the mouth might lead to enamel changes or periodontal tissue destruction, especially after 14 days of use.